2021
DOI: 10.1177/09612033211028658
|View full text |Cite
|
Sign up to set email alerts
|

Principles of pediatric lupus nephritis in a prospective contemporary multi-center cohort

Abstract: Lupus nephritis (LN) is a life-threatening manifestation of systemic lupus erythematosus (SLE) and is more common in children than adults. The epidemiology and management of childhood-onset SLE (cSLE) have changed over time, prompting the need to reassess expected outcomes. The purpose of this study is to use the Childhood Arthritis and Rheumatology Research Alliance (CARRA) prospective registry to validate historical principles of LN in a contemporary, real-world cohort. After an extensive literature review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Use of B cell–depleting therapies also became increasingly common—up to 25% of lupus nephritis patients in the CARRA registry's contemporary pediatric lupus cohort have received rituximab (9). There have also been several initiatives to develop standards for pediatric lupus care, including international consensus recommendations for quality indicators in 2013 (10), and European guidelines for management of pediatric lupus in 2016 (11,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of B cell–depleting therapies also became increasingly common—up to 25% of lupus nephritis patients in the CARRA registry's contemporary pediatric lupus cohort have received rituximab (9). There have also been several initiatives to develop standards for pediatric lupus care, including international consensus recommendations for quality indicators in 2013 (10), and European guidelines for management of pediatric lupus in 2016 (11,21).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 2 decades, there have been several advances in the care of children with lupus, including an expansion of therapeutic options and increasing emphasis on quality metrics that may be associated with improved renal outcomes (7). Mycophenolate mofetil (MMF) has become a mainstay of therapy for pediatric lupus nephritis (8), and the use of B cell-depleting therapies has also become increasingly common (9). Simultaneously, several consensus guidelines for management of pediatric lupus have been released (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Our subgroup analysis indicated that young patients with SLE were less likely to develop end-stage renal disease (ESRD). Another epidemiological investigation found that most children with LN had unchanged or normal kidney function, and that ESRD was rare ( Vazzana et al, 2021 ). In addition, the probability of death from active SLE was much lower in children than adult men ( Brunner et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data are limited on the comparative effectiveness of most diagnostic and management approaches in childhood SLE. Up to 20% of all SLE cases are diagnosed before age 18 years (1)(2)(3)(4)(5)(6), and 35%-70% develop kidney involvement (2,3,7,8). Lupus nephritis develops earlier and behaves more aggressively in childhood SLE compared with adult-onset SLE (9).…”
Section: Introductionmentioning
confidence: 99%